"State Analysis from Below" and Political Dynamics in Egypt after 2011. (9th February 2015) - Harders, Cilja
Abstract : Political scientists have struggled to understand the unexpected 2011 mass mobilizations in the Middle East and North Africa as well as ensuing sociopolitical transformations. Functionalist and regime-centered approaches in particular have been unable to grasp dynamics of mobilization and change on the ground. I argue in this short essay that "state analysis from below" helps us to better understand the underlying causes of the 2011 uprisings, the dynamics of ensuing power struggles, and sociopolitical microstructures of political mobilization and demobilization.